2015
DOI: 10.1589/jpts.27.805
|View full text |Cite
|
Sign up to set email alerts
|

The effects of whole body vibration on static balance, spinal curvature, pain, and disability of patients with low back pain

Abstract: [Purpose] The purpose of this study was to investigate the impact of whole body vibration (WBV) on static balance, spinal curvature, pain, and the disability of patients with chronic lower back pain. [Subjects and Methods] The subjects were of 40 patients, who were randomly assigned to WBV and control groups. Twenty-five minutes of lumbar stability training and 5 minutes of WBV were conducted for the WBV group, and 30 minutes of lumbar stability training was conducted for the control group. The training was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 18 publications
0
50
1
1
Order By: Relevance
“…To date, no clear distinction is indicated between high and low frequencies. The vibration frequency of lumbar abdomen is mostly below 20 Hz, and the results showed that such value could relieve pain in patients with CLBP and reduce the dysfunction index [10,30] . In current studies, 15 Hz was considered as high frequency compared with 5 Hz and 10 Hz.…”
Section: Effect Of Different Frequencies On Lumbar-abdominal Muscle Amentioning
confidence: 99%
“…To date, no clear distinction is indicated between high and low frequencies. The vibration frequency of lumbar abdomen is mostly below 20 Hz, and the results showed that such value could relieve pain in patients with CLBP and reduce the dysfunction index [10,30] . In current studies, 15 Hz was considered as high frequency compared with 5 Hz and 10 Hz.…”
Section: Effect Of Different Frequencies On Lumbar-abdominal Muscle Amentioning
confidence: 99%
“…Es wird über eine optimierte Regeneration nach körperlichem Training [7,[19][20][21], eine gesteigerte Muskelfunktion [22][23][24] und ein verbessertes Gleichgewicht [25][26][27][28][29][30][31] berichtet. Häufige klinische WBV-Anwendungen mit orthopädischen Hintergrund sind v. a. bei älteren PatientInnen und Frauen mit Osteoporose, Arthritis, Frakturen, Rücken-/Hüft-/Kniebeschwerden, neurologischen Erkrankungen oder Schmerzen zu finden, um die neuromuskuläre Leistungsfähigkeit, Stabilität und Mobilität positiv zu beeinflussen [8,[32][33][34][35][36][37][38][39].…”
Section: Mechanische Schwingungstherapie Im Klinischen Einsatzunclassified
“…The frequency of 40 Hz was selected to promote improvements in motor skills, through the increase in joint range, increased strength, and muscle fiber recruitment, to supply interneuron activities to the skin and receptors in the spinal cord, which reduce pain signals across C nerve fibers and increase the metabolic rate and blood flow (Kim et al, 2015;Yang and Seo, 2015).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Recent studies recommend the use of vibration therapy to relieve manifestations of pain and functional impairment (Aman et al, 2015;Yang and Seo, 2015), attenuate of muscle tension and muscle soreness (Veqar and Imtiyaz, 2014), fix neurological disorders (Silva et al, 2011), improve balance and proprioception (Martínez et al, 2013) and improve cardiovascular conditions (Naghii et al, 2012).…”
Section: Introductionmentioning
confidence: 99%